2008
DOI: 10.1007/s10658-008-9381-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal impact of fungicide spray strategies on fungicide sensitivity of Mycosphaerella graminicola in winter wheat

Abstract: Field experiments, involving various fungicide strategies with pyraclostrobin and/or epoxiconazole were carried out in 2004 and 2005, with the overall purpose of monitoring the evolution of fungicide sensitivity in Mycosphaerella graminicola on different isolates per leaf, leaf levels at different points of time, and points in the field. Sensitivity was assessed on single isolates by means of epoxiconazole EC 50 -values, and monitoring of the G143A-mutation, which confers strobilurin resistance. In both years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In this case one "at risk" opposes selection against the other. Although a recent modelling exercise showed that a mixture of two high resistance risk partners enhanced the life of both fungicides (Hobbelen et al 2013), experimental evidence supporting use of just "at risk" partners is limited to a few studies ((Brent et al 1989;Lorenz et al 1992;Gisi et al 2005;Thygesen et al 2009). …”
Section: Managing Resistance In Cropsmentioning
confidence: 99%
“…In this case one "at risk" opposes selection against the other. Although a recent modelling exercise showed that a mixture of two high resistance risk partners enhanced the life of both fungicides (Hobbelen et al 2013), experimental evidence supporting use of just "at risk" partners is limited to a few studies ((Brent et al 1989;Lorenz et al 1992;Gisi et al 2005;Thygesen et al 2009). …”
Section: Managing Resistance In Cropsmentioning
confidence: 99%
“…However, in many of these studies resistant strains were either introduced [4], [6], [13] or were already present at a significant frequency at the start of experiments [7], [9], [14]. As even a frequency of 1% represents a large population of resistant lesions, these studies describe the selection phase in the evolution of fungicide resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Berlese and De Toni . However, the repeated use of a particular fungicide class is not always associated with a decreased sensitivity . This creates a complex scenario, which is usually approached at the theoretical level to establish a relationship between fungicide spray programs and the possible evolution of resistance in the field …”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, the repeated use of a particular fungicide class is not always associated with a decreased sensitivity. 7,8 This creates a complex scenario, which is usually approached at the theoretical level to establish a relationship between fungicide spray programs and the possible evolution of resistance in the field. [9][10][11][12] To date, no multi-year studies on the dynamics of pathogen populations in real field conditions, where single-site fungicides are applied according to anti-resistance criteria, are available.…”
Section: Introductionmentioning
confidence: 99%